Base-base and deoxyribose-base stacking interactions in B-DNA and Z-DNA: a quantum-chemical study - Sponer, J; Gabb, H A; Leszczynski, J; Hobza, P (Biophysical journal, 1997)
Base-stacking interactions in canonical and crystal B-DNA and in Z-DNA steps are studied using the ab initio quantum-chemical method with inclusion of electron correlation. The stacking energies in canonical B-DNA base-pair steps vary from -9.5 kcal/mol (GG) to -13.2 kcal/mol (GC). The many-body nonadditivity term, although rather small in absolute value, influences the sequence dependence of stacking energy. The base-stacking energies calculated for CGC and a hypothetical TAT sequence in Z-configuration are similar to those in B-DNA. Comparison with older quantum-chemical studies shows that they do not provide even a qualitatively correct description of base stacking. We also evaluate the base-(deoxy)ribose stacking geometry that occurs in Z-DNA and in nucleotides linked by 2',5'-phosphodiester bonds. Although the molecular orbital analysis does not rule out the charge-transfer n-pi* interaction of the sugar 04' with the aromatic base, the base-sugar contact is stabilized by dispersion energy similar to that of stacked bases. The stabilization amounts to almost 4 kcal/mol and is thus comparable to that afforded by normal base-base stacking. This enhancement of the total stacking interaction could contribute to the propensity of short d(CG)n sequences to adopt the Z-conformation.
Keywords: kalorimetrie; Models, Molecular; sekvence nukleotidů; oligodeoxyribonukleotidy; Deoxyribose; Potentiometry; chemické modely; zastoupení bazí; termodynamika; potenciometrie; Calorimetry; Base Composition; molekulární modely; deoxyribosa; DNA; Quantum Theory; Thermodynamics; Base Sequence; Models, Chemical; kvantová teorie; konformace nukleové kyseliny; Nucleic Acid Conformation; Oligodeoxyribonucleotides